Mergers & acquisitions : Microsoft Corporation vs Box Inc. - Correia, Francisco Rocha Barros Peres (2016)
Technology’s rapid shifts have put cloud computing as the edge companies must have in order to succeed and stay relevant in an industry where innovation is key. Realizing this, Microsoft’s CEO, Satya Nadella, changed the technology giant’s strategic focus towards, what he calls, a “cloud-first, mobile-first world”. In this context comes Box – a highly promising cloud-based enterprise content collaboration platform that allows organizations to securely manage their content and collaborate internally and externally. Its platform is considered superior to that of its peers, allowing the recently listed company to gather a large user base, with over 39 million people and 50.000 organizations using its service. However, its high customer acquisition cost has been dampening its margins and postponing profitability until 5 years time, drifting many investors away from the company, making its share price to drop in recent months. This makes Box a very desirable target for Microsoft’s envisioned cloud-first world, as Microsoft has all the needed expertise to make Box profitable in the near-term and create the leader in the crowded cloud computing industry. This dissertation will evaluate the possibility of the acquisition of Box by Microsoft. The proposal is supported by a review of the main literature on M&A and valuation, an extensive industry and company analysis, and a valuation of each individual firm and its combination. It is concluded, based upon the several analyses conducted throughout the dissertation, that Microsoft should acquire Box for $2,9 billion in an all-cash deal, a 35% premium over its market capitalization.